The “Ethno-Political Multiple”: Colonial Investigations of Indigenous Polities in East Timor - Roque, Ricardo (2022)
This article analyzes colonial investigations of the indigenous polities designated as reinos (kingdoms) in East Timor during the long nineteenth century. Effective governance of the reinos was paramount to the colonial state. Accordingly, they became a focus of the intellectual activities of Portuguese officials and administrators. The article examines the knowledge forms—enumerative, historiographic, and ethnographic—used to study and manage these diverse polities as an “ethno-political multiple”; that is, the colonial notion according to which the indigenous sociopolitical world was conceived of, investigated, and acted upon as a plural reality, simultaneously one and multiple.